Segniliparus rugosus from the sputum of a child with cystic fibrosis in Ecuador: challenges in bacterial identification. (May 2020) - Zurita, J.; Sevillano, G.; González, C.; Lascano, Y.
Abstract: Using sequencing analyses of the 16S rRNA gene, we identified Segniliparus rugosus in an 8-year-old child with cystic fibrosis. We describe the difficulties we encountered in identifying this bacterium. To the best of our knowledge, this is the first reported case of S. rugosus in Ecuador.